2023
DOI: 10.3390/cancers15133324
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of hsa-miR-181a-5p, hsa-miR-143-3p, hsa-miR-132-3p and hsa-miR-23a-3p as Biomarkers in Colorectal Cancer—Relationship to the Body Mass Index

Abstract: This work aims to investigate the expression levels of four preselected miRNAs previously linked to cancer and/or obesity, with the purpose of finding potential biomarkers in the clinical management of CRC developed by patients showing different BMI values. We analyzed samples from a total of 65 subjects: 43 affected by CRC and 22 without cancer. Serum and both subcutaneous and omental adipose tissues (SAT and OAT) were investigated, as well as tumor and non-tumor colorectal tissues in the case of the CRC pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
(74 reference statements)
1
0
0
Order By: Relevance
“…In the current study, hsa-miR-181a-5p showed a significant over-expression in the CRC group compared to controls. In contrast to Tesolato et al [22] who reported a down-regulation of hsa-miR-181a-5p in CRC patients compared to the control group, the findings of the current study concur with that of Zhang et al [18] who demonstrated a significantly higher miR-181a-5p expression level in CRC plasma exosomes.…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, hsa-miR-181a-5p showed a significant over-expression in the CRC group compared to controls. In contrast to Tesolato et al [22] who reported a down-regulation of hsa-miR-181a-5p in CRC patients compared to the control group, the findings of the current study concur with that of Zhang et al [18] who demonstrated a significantly higher miR-181a-5p expression level in CRC plasma exosomes.…”
Section: Discussionsupporting
confidence: 82%